Adverse Drug Events After Hospital Discharge in Older Adults: Types, Severity, and Involvement of Beers Criteria Medications. Issue 11 (1st October 2013) - Kanaan, Abir O.; Donovan, Jennifer L.; Duchin, Nerissa P.; Field, Terry S.; Tjia, Jennifer; Cutrona, Sarah L.; Gagne, Shawn J.; Garber, Lawrence; Preusse, Peggy; Harrold, Leslie R.; Gurwitz, Jerry H.
<x xml:space="preserve">Abstract</x> Objectives To characterize adverse drug events (ADEs) occurring within the high‐risk 45‐day period after hospitalization in older adults. Design Clinical pharmacists reviewed the ambulatory records of 1, 000 consecutive discharges. Setting A large multispecialty group practice closely aligned with a Massachusetts‐based health plan. Participants Hospitalized individuals aged 65 and older discharged home. Measurements Possible drug‐related incidents occurring during the 45‐day period after hospitalization were identified and presented to a pair of physician‐reviewers who classified incidents as to whether an ADE was present, whether the event was preventable, and the severity of the event. Medications implicated in ADEs were further characterized according to their inclusion in the 2012 Beers Criteria for Potentially Inappropriate Medication Use in Older Adults. Results At least one ADE was identified during the 45‐day period in 18.7% (n = 187) of the 1, 000 discharges. Of the 242 ADEs identified, 35% (n = 84) were deemed preventable, of which 32% (n = 27) were characterized as serious, and 5% (n = 4) as life threatening. More than half of all ADEs occurred within the first 14 days after hospitalization. The percentage of ADEs in which Beers Criteria medications were implicated was 16.5% (n = 40). Beers criteria medications with both a high quality of evidence and strong strength of recommendation were implicated in 6.6% (n = 16) of the ADEs. Conclusion ADEs are common and often preventable in older adults after hospital discharge, underscoring the need to address medication safety during this high‐risk period in this vulnerable population. Beers criteria medications played a small role in these events, suggesting that efforts to improve the quality and safety of medication use during this critical transition period must extend beyond a singular focus on Beers criteria medications.